Pengaruh Generasi Milenial Terhadap Experience Pengunjung pada Smart Banking Lounge: The Influence of the Millennial Generation on Visitor Experience in Smart Banking Lounge. - Radityotomo, Revaya; Astuti, Susy Budi; Wardhana, Mahendra (Program Studi Desain Interior Unikom, 2024)
Millennial generation, as technology-savvy users, possesses unique consumer preferences, openness to innovation, and demands for a comfortable and efficient user experience. Despite the advancements in digital banking technology, an increasing number of customers are reluctant to visit physical banks, resulting in a decline in visitor numbers. Therefore, this research aims to provide an understanding of the dynamics of the relationship between the millennial generation and visitor experiences in Smart Banking Lounges. The research methodology applied is a comparative descriptive method with an Omni-channel approach, where all channels are integrated to deliver the best experience to visitors. Data is obtained through literature studies on banking in Indonesia, digital banking, requirements for digital banking media in physical banks, banking activities, and the millennial generation. In the discussion, the research identifies the influence of the millennial generation on Smart Banking Lounges, including high technology skills, preferences for efficiency and speed, as well as the desire for personalized experiences and social engagement. This research provides valuable insights for the banking industry in designing and enhancing Smart Banking Lounges to be more responsive to the preferences and expectations of the millennial generation, thereby improving competitiveness and overall banking service quality.